Rural Development through Panchayati Raj Institutions in Jaipur District: Evaluation of Policy and Practical Challenges : जयपुर जिले में पंचायती राज संस्थाओं के माध्यम से ग्रामीण विकास: नीतिगत एवं व्यावहारिक चुनौतियों का मूल्यांकन - Verma, Man Mohan; Nair, Anila (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
In India, Panchayati Raj Institutions have been granted constitutional status to strengthen the process of rural development. Through the 73rd Constitutional Amendment Act, 1992, local self-governance was empowered and the responsibility for implementing development schemes was decentralized to the village level. The objective of this research paper is to analyze the role of Panchayati Raj Institutions in rural development in Jaipur district of Rajasthan and to evaluate the policy and practical challenges faced by them. The study finds that Panchayats play an important role in promoting rural infrastructure, social welfare, employment generation, and public participation. However, despite these contributions, issues such as financial dependency, administrative complexities, political interference, and lack of technical expertise affect their effective functioning. Abstract in Hindi Language: भारत में ग्रामीण विकास की प्रक्रिया को सुदृढ़ बनाने हेतु पंचायती राज संस्थाओं को संवैधानिक दर्जा प्रदान किया गया है। 73वें संविधान संशोधन अधिनियम, 1992 के माध्यम से स्थानीय स्वशासन को सशक्त किया गया तथा विकास योजनाओं के क्रियान्वयन की जिम्मेदारी ग्राम स्तर तक विकेन्द्रीकृत की गई। प्रस्तुत शोध-पत्र का उद्देश्य राजस्थान के जयपुर जिले में पंचायती राज संस्थाओं की ग्रामीण विकास में भूमिका का विश्लेषण करना तथा उनके समक्ष उपस्थित नीतिगत एवं व्यावहारिक चुनौतियों का मूल्यांकन करना है। अध्ययन में यह पाया गया कि पंचायतें ग्रामीण आधारभूत संरचना, सामाजिक कल्याण, रोजगार सृजन एवं जनभागीदारी को बढ़ावा देने में महत्वपूर्ण भूमिका निभाती हैं। इसके बावजूद वित्तीय निर्भरता, प्रशासनिक जटिलताएँ, राजनीतिक हस्तक्षेप तथा तकनीकी दक्षता की कमी जैसी समस्याएँ इनके प्रभावी कार्यान्वयन को प्रभावित करती हैं। Keywords: पंचायती राज, ग्रामीण विकास, विकेन्द्रीकरण, स्थानीय स्वशासन, जयपुर जिला